Blessing (Barakah) as a Social Capital of the Haul Guru Sekumpul: Anthropological and Religious Perspectives - Rahmad Kurniawan; Ilfi Nur Diana; Segaf; M. Riza Hafizi (Center for Research and Development of Religious Literature and Heritage, 2025)
This study examines the concept of Barakah within the Haul (annual commemoration) of Guru Sekumpul by addressing a key research gap: although Barakah is widely invoked in Islamic discourse, its operational meaning and socio-economic manifestations in contemporary Muslim communities remain underexplored. The research investigates how Barakah functions as spirituality-based social capital that shapes collective behavior and community welfare in Banjar society, South Kalimantan. Using textual data from fatwas, documents, and interviews, complemented by ethnographic observations, the study applies teleological interpretation and content analysis to identify how Barakah is articulated, practiced and socially reproduced during the Haul. The findings indicate, first, that Barakah is conceptualized not merely as divine favor but as an integrated moral framework linking livelihood, emotional composure and communal benefit. Second, Barakah operates as a catalyst for voluntary service, trust-building and large-scale mutual aid, thereby strengthening the community’s social capital. Third, the Haul further ‘institutionalizes’ Islamic economic values, particularly maslahah and falah, hrough routinized acts of charity and cooperation. These insights demonstrate that Barakah serves both spiritual and socio-economic functions, offering an empirical model of how religious rituals can reinforce ethical development practices.